MARKETING COMMUNICATION INNOVATION OF FRESH FRUIT AND VEGETABLES (FFV) MODERN RETAIL LOCAL SUPPLIER: COMPETITIVENESS OF SMALL HOLDER TO ENTER MODERN RETAIL - Hesty Nurul Utami; Agriani Hermita Sadeli (Universitas Padjadjaran, 2014)
Modern retail rapid development is an opportunity for fruit and vegetable farmers to fulfill consumerretail business demand. This research give an insight of how marketing communication innovation suggested forlocal FFV supplier in order to enter modern retail by concerning their competitiveness through modern retailpoint of view and adjusted with modern retail marketing decision. It applies qualitative design through casestudy at Retail XYZ Group. The main FFV supplier criteria appointed by the company are supplier price productoffering, product quantity, quality and continuity. Overall, almost all of local FFV supplier marketing criteria isperceived worst than importer in terms of durability, quantity, service level, after post harvest handling, R&D, andcommodity attribute. An incremental marketing communication innovation could be done via direct partnershipwith small holders who are able to meet retail FFV requirements in commodity quantity, quality, continuity, postharvest handling, durability, research and development facility, product sourcing and availability throughoutseason, and deliver service excellent. This is an opportunity for the small holder to build a long term relationshipmarketing with modern retail.